Penyisihan Kadar Fosfat Pada Limbah Cair Laundry Menggunakan Biokoagulan Cangkang Keong Mas (Pomacea Canaliculata) - Rio Patrianov Nugroho; Syarfi Daud; Jecky Asmura (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Biocoagulant is a natural coagulant that has an active substance and has a role as cationic which is able to bind colloidal particles in water. Chitosan is a non-toxic, easy-to-degrade and polyelectrolyte biocogulant that can be found in crustacean animals especially in s (Pomacea Canaliculata). The availability of shell waste has a huge potential to be used as raw material for making chitosan. High concentration of detergent in water can cause water quality to decrease and environmental pollution in the form of increase of phosphate level, so that the previous processing is needed by using coagulation-flocculation method. The research process was done gradually starting from the extraction of shells to chitosan by deproteination process, demineralization, and deacetylation, followed by Coagulation-flocculation method. The study was conducted by varying the dose of coagulant by 200 mg / L, 250 mg / L, 300 mg / L, 350 mg/L and 400 mg / L. The effluent was then analyzed by the laboratory, for phosphate refers to SNI 06-6989.31-2005. The result of the analysis was then compared with the PERMENLH / 5/2014 quality standard. Based on the laboratory results, after analyzing the concentration of the parameters tested, it showed that the maximum allowance of phosphate parameters were 67.57% respectively at 300 mg / L, coagulant dose with stirring speed of 150 rpm for 2 min and 60 rpm for 15 min followed by deposition for 30 min. The result of the analysis is compared with the PERMENLH / 5/2014 quality standard. the results of the analysis for phosphate values have met the quality standard, where the standard limit of laundry liquid waste for phosphate 2 mg/L.Keywords: Biocoagulant, chitosan, coagulation-flocculation, phosphate